Acacia nilotica leaf meal - potential supplement to 25% dorper crosses of local sheep fed a basal diet of natural pasture hay. Issue 8 (August 2022) - Bekele, Wondimagegne; Kassa, Getachew; Taddes, Teklewold; Girma, Muluken; Mengistu, Alemayehu; Assefa, Getnet
Abstract: This research was conducted to evaluate the replacement potential of Acacia nilotica dried leaf meal for Noug Seed Cake (NSC) to supplement low quality grass hay in the diet of crossbred sheep (25% Dorper). In doing so, four treatments were set up in such a way that 0%, 33%, 67%, and 100% NSC is replaced with dried leaf of Acacia nilotica from a conventional supplement while the treatments were kept isonitrogenous. The experiment was set up in a Randomized Complete Block Design, with initials weight used as the blocking factor. Twenty animals were allocated to the four treatments. The experiment consisted of hundred days of feeding trial followed by evaluation of carcass components at the end. In addition, the experimental feed ingredient was studied in vitro for gas production, methane (CH4 ) production, fractional rate of degradation (Kd), and in vitro dry matter digestibility (IVDMD). In view of chemical composition, grass hay contained lower crude protein (CP = 3.2% DM) and high cell wall contents that makes it lower quality feed. On the other hand, Acacia nilotica leaf meal was moderate in quality (CP = 14.3% DM) that can support moderate level of ruminant production. In an in vitro study, Acacia nilotica was found to have lower (P < 0.01) levels of CH4, total gas, kd, and IVDMD compared to the other feed ingredients. This indicates that tannin have an effect on Acacia nilotica feed. Partial and complete replacement of NSC with Acacia nilotica leaf meal significantly increased total dry matter intake (TDMI) (P < 0.001). Average daily gain (ADG) and dressing percentage was also higher for leaf meal supplemented groups. Hot carcass weight was in the range of 14.8–17.8 kg, which is higher than the national average carcass weight for Ethiopian sheep, and it was also found to be higher when NSC was partially (33%) as well as completely replaced by the leaf meal. In general, NSC can be replaced either partially or completely with Acacia nilotica leaf meal in the diet of 25% Dorper crosses while weight gain as well as carcass yield is promoted. The maximum inclusion level of Acacia nilotica was 61.3% or 319.2 g per day for 25% Dorper cross sheep fed natural pasture hay as a basal diet. Abstract : Acacia nilotica leaf meal; Dorper cross sheep; Carcass weight, Weight gain; Noug seed cake.